Onomatopoeia Translation Techniques in the Hunger Games Trilogy Novel into Indonesian - Syuqaira El Humaira; Hayatul Cholsy (Institut Agama Islam Negeri Palopo, 2021)
Onomatopoeia is a linguistic term that can be interpreted as a vocabulary that is formed based on the sound or sounds issued by the word. Each language has a distinctive onomatopoeia that is adjusted with the socio-cultural conditions of the speakers of that language. This affects the onomatopoeic translation due to cultural differences between the source language and the target language, such as from English into Indonesian. This study aims to analyze the techniques used in onomatopoeic translation in the trilogy novel The Hunger Games by Suzanne Collins translated into Indonesian by Desy Rachmaindah. In analyzing the data, the writer uses the translation technique of Molina & Albir (2002). The results of this study indicate that onomatopoeic translation used 9 translation techniques and literal translation techniques dominated because it was translated according to the meaning based on the dictionary.